2020
DOI: 10.1002/jctb.6631
|View full text |Cite
|
Sign up to set email alerts
|

Green sustainable technology for biotreatment of actual dairy wastewater in constructed wetland

Abstract: BACKGROUND Due to the environmental problems caused by food processing wastewaters and their complex and expensive treatment methods, it becomes mandatory to seek a sound, sustainable and environmentally friendly solution such as constructed wetland (CW). This study aimed to investigate the potential of treating real dairy wastewater in CW. Six horizontal subsurface flow CW microcosms were set up using different conventional and cost‐effective supporting media, which were gravel, soil and sand. All the CWs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…It is important to note that this wetland differs in configuration and plant species from other studies that have reported higher removal rates ranging from 30% to 99% [47]. These results are consistent with what was reported by Mohammed & Ismail [50], who achieved TSS removal efficiencies with Canna indica in a microcosm within a range of 99.2% to 93.4% for a similar type of water. In a laboratory-scale study that employed vertical flow-constructed wetlands to treat dairy wastewater, Canna indica plantations Significant differences (p ≤ 0.001) in average removal efficiencies were observed between the treatments.…”
Section: Total Suspended Solids (Tss)supporting
confidence: 89%
“…It is important to note that this wetland differs in configuration and plant species from other studies that have reported higher removal rates ranging from 30% to 99% [47]. These results are consistent with what was reported by Mohammed & Ismail [50], who achieved TSS removal efficiencies with Canna indica in a microcosm within a range of 99.2% to 93.4% for a similar type of water. In a laboratory-scale study that employed vertical flow-constructed wetlands to treat dairy wastewater, Canna indica plantations Significant differences (p ≤ 0.001) in average removal efficiencies were observed between the treatments.…”
Section: Total Suspended Solids (Tss)supporting
confidence: 89%
“…Despite having been initially designed to treat domestic wastewater on a small scale, recently, CWs have been used to treat effluents from agriculture and dairy industries, winery, tannery, paper, and pulp, among others. Regarding industrial effluents and their reuse, CWs contribute to a system that can treat water containing high organic loads and different contaminants, while producing a small amount of sludge [28,29]. The efficiency of the removal of the main contaminants of domestic and municipal wastewater in CWs is comparable to that of modern technologies of wastewater treatment, such as the activated sludge process (ASP), sequence batch reactor (SBR), mobile bed biofilm reactor (MBBR), upflow anaerobic sludge blanket (UASB), etc.…”
Section: Treatment Of Domestic Wastewater and Industrial Effluents By...mentioning
confidence: 99%
“…Ref. [97] used this species to treat dairy-farm effluents with high concentrations of organic matter and obtained very high COD removal. Beyond the improvement of water quality, C. indica also contributes to the aesthetic value of the locations.…”
Section: Cannaceaementioning
confidence: 99%